К вопросу о второй славянской палатализации - Поляков, Олег Всеволодович (Kalbotyra, 1997)
The article deals with the problem of the second Slavic palatalisation. The discovery of the effect of S. Gluskina and А. Zaliznjak’s detailed investigation of birch bark letters deny the Common Slavic character of the second Slavic palatalisation. The structural analysis of the facts and the investigation of the Pskov dialects by V. Čekmonas, who shows their mixed character, give reason to support the classical doctrine that the second palatalisation was а common one for all Slavic languages.